Locomotor demands of 30-15 Intermittent Fitness Test, Yo-Yo Intermittent Recovery Test, and VAMEVAL test and comparisons with regular locomotor demands in training sessions and matches: a study conducted in youth male soccer players - Clemente, Filipe (2022)
Purpose. The study aim was 2-fold: (i) characterize and compare the locomotor demands of 30-15 Intermittent Fitness Test (30-15IFT), Yo-Yo Intermittent Recovery Test level 1 (YYIRT), and VAMEVAL test; (ii) compare the locomotor demands of these progressive multistage tests with those of training sessions and matches in youth soccer players. Methods. A descriptive case study lasting 3 weeks was performed to implement the tests once and to monitor the locomotor demands in training sessions and matches. Overall, 12 soccer players (age: 18.21 ± 0.34 years) from the same team partici pated after consideration of inclusion criteria. A Global Positioning System unit was used for each player over the training sessions, matches, and multistage tests to monitor locomotor demands. The following outcomes were extracted: total distance; peak speed; distances covered at 3.00–6.99 km/h (Z1), 7.00–10.99 km/h (Z2), 11.00–14.99 km/h (Z3), 15.00–18.99 km/h (Z4), and 19.00 km/h (Z5); accelerations at 0.50 to 0.99 m/s2 and 1.00 to 1.99 m/s2 ; and decelerations at –0.99 to –0.50 m/s2 and –1.99 to –1.00 m/s2 . Results. Significant differences between progressive multistage tests were found in total distance (p = 0.028); distances covered at Z1 (p < 0.001), Z2 (p < 0.001), Z3 (p < 0.001), Z4 (p = 0.009), and Z5 (p = 0.044); accelerations at 0.50 to 0.99 m/s2 (p < 0.001) and 1.00 to 1.99 m/s2 (p < 0.001); and decelerations at –0.99 to –0.50 m/s2 (p < 0.001) and –1.99 to –1.00 m/s2 (p < 0.001). The total distance of the 3 progressive multistage tests may vary between 39% and 49% of a middle training session (match-day 3). However, as for intense locomotor demands at distance covered at Z4, 2 of the field-based tests ex ceeded a typical match-day 3 between 308 m (+83%) in 30-15IFT and 112 m (+30%) in YYIRT. Conclusions. The results suggests that 30-15IFT is more demanding considering high-intensity locomotor activities, while YYIRT and VAMEVAL are more demanding considering moderate locomotor demands. Moreover, specific adjustments in training sessions must be conducted, especially when introducing 30-15IFT and YYIRT since they may exceed the typical doses of distances covered at 11.00–14.99 km/h and 15.00–18.99 km/h.